MEMBINA KELUARGA BAHAGIA SEBAGAI UPAYA PENURUNAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DALAM PERSPEKTIF AGAMA ISLAM DAN UNDANG-UNDANG - Nurmadiansyah, M. Thoriq (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
This article talks about efforts to foster happy families to anticipate domestic violence. The perspective discussed would be in the in the views of Islam and the law in Indonesia. The existence of domestic violence is a fact in the social life of Indonesian families, many women and children have fallen victim thereto. Domestic violence could be avoided and reduced is the commitment constructed between husband and wife is consistent with the teachings of Islam and the relevant legal provisions. A proper understanding of respective roles, rights and obligationsÂ would lead to happy families and the extinction of domestic violence.